Pengaruh Pupuk Belerang Dengan Bokashi Eceng Gondok (Eichornia crassipes Mart. Solm) Terhadap pH, S Tersedia, Fe Tersedia, dan Hasil Tanaman Padi Sawah (Oryza sativa L.) Pada Vertisols - Emma Trinurani Sofyan (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2014)
The objective of this experiment was to study the influence of sulfur fertilizer and water hyacinth bokashi on soil pH, available-S, available-Fe, and yield of paddy rice  grown on Chromic Hapluderts. The experiment was conducted from November 2010 to February 2011 at Green House of Balai Pelatihan Pertanian Cihea Cianjur, elevated at 298 metres above sea level. The experiment was arranged in a Randomized Completely Block Design of Factorial Pattern. The first factor was sulfur fertilizer comprises of : without sulfur (s0), 20 kg ha-1 S (s1), 40 kg ha-1 S (s2), and 60 kg ha-1 S (s4). The second factor was water hyacinth bokashi comprises of : without bokashi (b0), 15 t ha-1 bokashi (b1), 30 t ha-1 bokashi (b2), and 45 t ha-1 bokashi (b3).  The result of experiment showed that there was an interaction effect between sulfur fertilizer and water hyacinth bokashi on available-S, and available-Fe, but not on pH and yield of paddy rice. Water hyacinth bokashi give an independent effect on yield of paddy rice.  The maximum dry seed weight (111.37 g pot-1 or 17.8 t ha-1) were achieve by 15.26 kg ha-1 S and 41.08 t ha-1 water hyacinth bokashi.